Optimization of key factors affecting hydrogen production from sugarcane bagasse by a thermophilic anaerobic pure culture - Lai, Zhicheng (BioMed Central, 2014)
BACKGROUND: Hydrogen is regarded as an attractive future energy carrier for its high energy content and zero CO(2) emission. Currently, the majority of hydrogen is generated from fossil fuels. However, from an environmental perspective, sustainable hydrogen production from low-cost lignocellulosic biomass should be considered. Thermophilic hydrogen production is attractive, since it can potentially convert a variety of biomass-based substrates into hydrogen at high yields. RESULTS: Sugarcane bagasse (SCB) was used as the substrate for hydrogen production by Thermoanaerobacterium aotearoense SCUT27/Δldh. The key parameters of acid hydrolysis were studied through the response surface methodology. The hydrogen production was maximized under the conditions of 2.3% of H(2)SO(4) for 114.2 min at 115°C. Using these conditions, a best hydrogen yield of 1.86 mol H(2)/mol total sugar and a hydrogen production rate (HPR) of 0.52 L/L · h were obtained from 2 L SCB hydrolysates in a 5-L fermentor, showing a superior performance to the results reported in the literature. Additionally, no obvious carbon catabolite repression (CCR) was observed during the fermentation using the multi-sugars as substrates. CONCLUSIONS: Considering these advantages and theimpressive HPR, the potential of hydrogen production using T. aotearoense SCUT27/Δldh is intriguing. Thermophilic, anaerobic fermentation using SCB hydrolysates as the medium by this strain would be a practical and eco-friendly process. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13068-014-0119-5) contains supplementary material, which is available to authorized users.